2011
DOI: 10.1016/s1473-3099(11)70054-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-prescription antimicrobial use worldwide: a systematic review

Abstract: In much of the world antimicrobial drugs are sold without prescription or oversight by health-care professionals. The scale and effect of this practice is unknown. We systematically reviewed published works about non-prescription antimicrobials from 1970-2009, identifying 117 relevant articles. 35 community surveys from five continents showed that non-prescription use occurred worldwide and accounted for 19-100% of antimicrobial use outside of northern Europe and North America. Safety issues associated with no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
670
4
16

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 771 publications
(748 citation statements)
references
References 116 publications
24
670
4
16
Order By: Relevance
“…Moreover, self-medication with this group of drugs is usually absolutely inadequate, especially when indicated by laypersons or reusing old prescriptions, increasing the risk of adverse reactions (16) . The students of this study reported the use of multivitamins, as also found among students in Recife (6) .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, self-medication with this group of drugs is usually absolutely inadequate, especially when indicated by laypersons or reusing old prescriptions, increasing the risk of adverse reactions (16) . The students of this study reported the use of multivitamins, as also found among students in Recife (6) .…”
Section: Discussionmentioning
confidence: 99%
“…The high number of antibiotic users is suggestive of a link between emergence of antibiotic resistant strains of microorganisms and misuse of the same. [19][20][21][22][23] Respondents of the survey have unused medicines for a variety of reason (Figure-3), the most common ones being not noticing the expiration date (32.70%), discontinuation of the medicine (22.27%) on the belief that it was not working or the patient was completely recovered and did not need to follow the full regimen, and fear of potential side effects (16.11%). Proper patient counselling on importance of following the regimen and chances of experiencing an adverse reaction to the drug may take care of most of the reasons for non-compliance.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with developed countries, where outpatient antimicrobials are largely restricted to prescriptiononly use, non-prescription access to antimicrobials is common in less affluent countries, resulting in uncontrolled use and self-medication [17,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%